On Pell and Pell-Lucas Generalized Octonions - TOKEŞER, Ümit; MERT, Tuğba; ÜNAL, Zafer; BİLGİCİ, Göksal (Turkish Journal of Mathematics and Computer Science, Association of Mathematicians, 2021)
In this study, we gave a generalization on Pell and Pell-Lucas octonions over the algebra $\mathbb{O}(a,b,c)$ where $a,b$ and $c$ are real numbers. For these number sequences, we obtain Binet formulas and gave some well-known identities such as Catalan's identity, Cassini's identity and d'Ocagne's identity.
Keywords: Matematik; Engineering; Pell octonion; Pell-Lucas octonion; Generalized octonion; Pell octonion; Pell-Lucas octonion; Mühendislik; Generalized octonion; Mathematical Sciences